Highly secured Android application based smartphone - Tan, Ngan Hong (2018)
The improvement of the mobile technology has been increasing rapidly in the past few years ever since the launch of mobile smart phone. The change of services from website to mobile platform can be seen increasing which give other option for the companies to provide to their customers. Nowadays, we can see the grow of smartphone users rapidly. The amount of confidential data transmitting has been increasing which the security is a very big concern. One of the biggest issues is the loss of data that many people are facing now in mobile security. In this report, it shows the development of the three mobile application. The used software call android studio and were written in java and xml language. The 3 applications are Chat, Food ordering and Private car hiring which are used to analyze 2 possible attack, buffer overflow and firmware attack. A countermeasure had been made and implemented with Advanced Encryption Standard (AES) to further enhance the security level on the applications.